2021
DOI: 10.1093/cid/ciab617
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) Outbreak Associated With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) P.1 Lineage in a Long-Term Care Home After Implementation of a Vaccination Program—Ontario, Canada, April–May 2021

Abstract: In a P.1 COVID-19 outbreak in long-term-care, vaccine effectiveness against SARS-CoV-2 infection was 52.5% (95%CI 26.9-69.8%) in residents and 62.2% (95%CI, 2.3-88.3%) in staff. VE against severe illness was 78.6% (95%CI 47.9-91.2) in residents. Two of 19 vaccinated resident cases died. Outbreak management required both vaccination and infection control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…1 ). Ultimately, with three grey literatures included, this final meta-analysis comprised 58 eligible studies, including 32 studies [ 14 , 15 , 17 20 , 23 48 ] for vaccine effectiveness and 26 studies [ 49 – 74 ] for vaccine safety. Characteristics of included studies are showed in Additional file 1 : Table S1, Additional file 2 : Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Ultimately, with three grey literatures included, this final meta-analysis comprised 58 eligible studies, including 32 studies [ 14 , 15 , 17 20 , 23 48 ] for vaccine effectiveness and 26 studies [ 49 – 74 ] for vaccine safety. Characteristics of included studies are showed in Additional file 1 : Table S1, Additional file 2 : Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…In an outbreak occurred in the north of Italy, with an infection rate of 45% among fully vaccinated individuals, the only variable associated with an increased risk of infection and death was age [ 14 ]. The authors highlighted that integrate vaccination with nonpharmacological measures still remains critical to the control of SARS-CoV-2 transmission in LTCFs setting, especially in the context of new more transmissible variants [ 11 , 13 , 14 ]. Even if viral load in infected vaccinated residents may be lower than that of unvaccinated, the residential environment itself poses some risk factors (closed spaces, specific care needs, proximity between residents and staff) that may facilitate the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Given that we have detected anti-Spike/RBD IgA in the serum and saliva of mRNA vaccinated participants, we examined whether IgA levels may be associated with protection against breakthrough infection. On 20th April 2021, an outbreak of P.1 lineage SARS-CoV-2 (gamma variant) was declared in a Toronto LTCH home 16 . The residents, who were all doubly vaccinated with mRNA-1273, were part of a separate serum antibody study following LTCH residents that included sampling of blood, but not saliva, at 2-4 weeks post-dose 2 (received on February 2, 2021).…”
Section: Resultsmentioning
confidence: 99%